1990
DOI: 10.1073/pnas.87.7.2833
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cloning of HLA-A,B cDNA by using the polymerase chain reaction: frequency and nature of errors produced in amplification.

Abstract: A method for cloning full-length HLA-A,B cDNA (1.1 kilobases) by using the polymerase chain reaction (PCR) is described. Six HLA-AB alleles (HLA-A2, -A25, -B7, -B37, -B51, and -B57) were cloned, and their structures were determined. Multiple PCR clones for each allele were sequenced to obtain both an accurate consensus sequence and an "authentic" done having that sequence. Sequences from 50 clones encoding five different alleles permit assessment of the frequency and nature of PCR-produced errors. These includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
155
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(162 citation statements)
references
References 28 publications
6
155
0
1
Order By: Relevance
“…Our results are consistent with previous studies of Taq DNA polymerase fidelity, which have shown that errors producing transition mutations are much more frequent than those that yield insertion͞deletions or transversions (2,3,10,(18)(19)(20). The sequence results summarized in Table 2 indicate that the MutHLS reaction can be used to effectively remove transition mutations, and although the sample size is small, probably frameshifts and some transversions as well.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our results are consistent with previous studies of Taq DNA polymerase fidelity, which have shown that errors producing transition mutations are much more frequent than those that yield insertion͞deletions or transversions (2,3,10,(18)(19)(20). The sequence results summarized in Table 2 indicate that the MutHLS reaction can be used to effectively remove transition mutations, and although the sample size is small, probably frameshifts and some transversions as well.…”
Section: Discussionsupporting
confidence: 81%
“…However, such errors can compromise genetic diagnostic methods based on mismatch detection with amplified DNA (8,9) and render results obtained with cloned PCR products problematic (10), with the severity of this problem increasing with DNA chain length and the number of doublings. By permitting removal of most mutant sequences generated during amplification, the method described here should prove useful in circumventing these difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a change from G to A on one strand cannot be distinguished from a change from C to T occurring on the complementary strand), the twelve possible nucleotide substitutions were grouped into six categories. Distributions of Taq errors reported by Dunning et al (1988) and Ennis et al (1990) were also included for comparison. Any possible bias resulting from the nucleotide composition of the target sequence was taken into account by introducing a weighting, achieved by recalculating the number of mutations for a 50 % GjC content, before the application of the G-statistic test for heterogeneity (Sokal & Rohlf, 1995).…”
Section: Categorizing Taq Mutationsmentioning
confidence: 99%
“…In both techniques, it cannot be determined whether the starting cDNA represents a true genomic copy, and will depend on the number of mRNA transcripts initially present. However, errors in amplification by the PCR are infrequent events that are more likely to occur late in amplification, resulting in mutations that are unique to a single clone (19). The error rate of the PCR as calculated by Ennis et al was 1 per 1421 nucleotides sequenced.…”
Section: Resultsmentioning
confidence: 99%